2002
DOI: 10.1073/pnas.152330199
|View full text |Cite
|
Sign up to set email alerts
|

Multiple label-free biodetection and quantitative DNA-binding assays on a nanomechanical cantilever array

Abstract: We report a microarray of cantilevers to detect multiple unlabeled biomolecules simultaneously at nanomolar concentrations within minutes. Ligand-receptor binding interactions such as DNA hybridization or protein recognition occurring on microfabricated silicon cantilevers generate nanomechanical bending, which is detected optically in situ. Differential measurements including reference cantilevers on an array of eight sensors can sequence-specifically detect unlabeled DNA targets in 80-fold excess of nonmatch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
485
2
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 575 publications
(503 citation statements)
references
References 21 publications
14
485
2
2
Order By: Relevance
“…29) The direction of the difference requires more positive stress on the facets than on the spherical regions, resulting in a relative inward displacement of the facets upon thiol adsorption. Similar values of stress have been measured in micromechanical cantilever measurements 50,51) of stresses generated by applying thiols to micrometer-thick Si membranes coated on one side with Au. The specific Au-S bonding causes stress on the coated surface of the cantilever, causing it to bend.…”
Section: In-situ Thiolation Of Au Nanocrystalsupporting
confidence: 73%
“…29) The direction of the difference requires more positive stress on the facets than on the spherical regions, resulting in a relative inward displacement of the facets upon thiol adsorption. Similar values of stress have been measured in micromechanical cantilever measurements 50,51) of stresses generated by applying thiols to micrometer-thick Si membranes coated on one side with Au. The specific Au-S bonding causes stress on the coated surface of the cantilever, causing it to bend.…”
Section: In-situ Thiolation Of Au Nanocrystalsupporting
confidence: 73%
“…In recent years a versatile platform for biodetection has been developed based on microfabricated arrays of silicon cantilevers 14,15,16,17,18,19,20,21 , each coated with a sensitive layer for molecular recognition, e.g. a gene specific oligonucleotide.…”
mentioning
confidence: 99%
“…Early reports on experiments gave high immobilization densities in the range of 0.13-0.17 chains/nm 2 ; 12,27 the displacement predictions corresponding to these densities are compared to reported experimental measurements 5,6,11,12,23 in Table II. In order to simplify comparison across different experiments, the predicted and measured displacements in the table are multiplied with the square of the aspect ratio h l À Á 2 of the cantilever used in the experiment.…”
Section: Comparison Of Numerical Prediction With Experimental Rementioning
confidence: 87%
“…Since this work, cantilever deflection due to ssDNA hybridization has been utilized as a validation experiment for new techniques, and cantilever deflection signals up to $100 nm have been reported for those experiments. [9][10][11][12]23 Hansen et al 7 also demonstrated that hybridizationinduced cantilever deflection can be used to discriminate base-pair mismatches with 20-nt and 25-nt probe DNA molecules. They used 10 nt DNA oligonucleotides as complementary target molecules, which contain either one or two internal mismatches.…”
Section: Introductionmentioning
confidence: 99%